Reviewing Employee Work Objectives From Compensation, Facilities and Work Environment, The Affect. - Hendrajaya, Hendrajaya; Syamsul Hadi; Henry Yuliamir; Dyah Palupiningtyas; Samtono, Samtono (Brilliant International Journal Of Management And Tourism, 2022)
There are still employee complaints that the compensation is not consistent with the concept of justice, the existing facilities at the research site are insufficient to perform community service duties, the facilities that require quantity and quality improvements. This study aims to prove the effect of compensation, facilities, and work environment on the job satisfaction of environmental employees in Kendal Regency. This study design is a descriptive study employed by quantitative analysis using SPSS version 17.0 for the Windows application. This study investigates the relationships between three independent effects — compensation (X1), facilities (X2), and work environment (X3) — and one dependent variable — job satisfaction (Y) with Approximately 114 Kendal Regency Environmental employees asministrated by the questionnaire to the respondents. The results show that there is a positive and significant effect of compensation, facilities, and work environment on the job satisfaction of Kendal Regency Environmental employees. The work environment is the variable that most dominantly influences the increase in job satisfaction of Kendal Regency Environmental employees because it has the highest beta value.